The Bible in discussion: Three recent South African publications on Scripture - Deist, Ferdinand (Hervormde teologiese studies, 1991)
Three recent South African books on Scripture from various theological trad itio n s and social circles (one Reformed, one Dutch Reformed and one Methodist, two by white authors and one by a black author) are discussed in order to evaluate their arguments and ascertain their points of difference, with a view to enhancing a meaningful South African dialogue on Scripture.